Influence of consumer trust, return policy, and risk perception on satisfaction with the online shopping experience - Hipólito, F.; Dias, Á.; Pereira, L. (Systems, 2025)
This study examines the interplay of consumer trust, return policies, and risk percep-tion in shaping satisfaction with online shopping experiences in a business to consum-er e-commerce context. Employing a conceptual model tested through Partial Least Squares-Structural Equation Modeling (PLS-SEM), it evaluates how these factors indi-vidually and collectively influence consumer satisfaction. The findings confirm that consumer trust reduces perceived risk and enhances shopping satisfaction. Contrary to expectations, attractiveness of free returns has no significant impact on either risk perception or satisfaction, while clear return policies positively influence satisfaction but not risk perception. Additionally, the study reveals a quadratic relationship be-tween risk perception and satisfaction, suggesting that an optimal level of perceived risk maximizes satisfaction, deviating from prior research advocating for minimal perceived risk. These results offer new insights into consumer behavior in online retail, highlighting the nuanced role of risk and emphasizing the strategic importance of trust and return policies. The paper concludes by discussing managerial implications and suggesting directions for future research.